Purification of genomic sequences from bacteriophage libraries by recombination and selection in vivo. - Seed, B (1983)
Cloned genes have been purified from recombinant DNA bacteriophage libraries by a method exploiting homologous reciprocal recombination in vivo. In this method 'probe' sequences are inserted in a very small plasmid vector and introduced into recombination-proficient bacterial cells. Genomic bacteriophage libraries are propagated on the cells, and phage bearing sequences homologous to the probe acquire an integrated copy of the plasmid by reciprocal recombination. Phage bearing integrated plasmids can be purified from the larger pool of phage lacking plasmid integrates by growth under the appropriate selective conditions.